Distributed Jenkins builds with containers - Deza, Alfredo; Deza, Alfredo; Gift, Noah (Pragmatic AI Solutions, 2021)
Distribute the load of Jenkins builds with a remote Docker instance or Kubernetes server in this 1-hour long tutorial Topics include: * Configure a remote Docker instance to interact with the master Jenkins server * Modify an existing job to use Docker to do builds using labels * Setup a remote kubernetes instance to connect to Jenkins with JNLP * Use the right container image to connect back to Jenkins as a remote container node.